Strategi Pengembangan Wisata Sawah dalam Meningkatkan Ekonomi Masyarakat dengan Pendekatan QSPM Desa Punden Rejo Kecamatan Tanjung Morawa Kabupaten Deli Serdang - Annisa, Annisa; Nasution, Annio Indah Lestari; Atika, Atika (Medan Resource Center, 2023)
This article aims to identify tourism development strategies for Punden Rejo Sawah in Tanjung Morawa District, Deli Serdang Regency. The descriptive analysis method is used to analyze the internal environment (strengths and weaknesses) and the external environment (opportunities and threats) of the tourist attraction. The results of the SWOT analysis present four main strategies: S-O (Educating about rice plants and improving facilities with agricultural concepts), W-O (Implementing a time-variety planting system and improving supervision), S-T (Improving facilities and quality), and W-T (Promoting tourism through social media). Through QSPM analysis, the S-O strategy was identified as the main priority for maximizing the tourism potential of Punden Rejo Rice Fields. The results of this research provide guidance for tourism managers to improve visitor experiences and local economic growth